Características agronómica de cuatro especies forrajeras arbóreas en el fundo de Zungarococha, Iquitos – Perú - Arce Bardales, Victor Reynaldo (2024)
In the humid tropical region, many forage tree and shrub species are adapted to provide an alternative for feeding ruminants and the National University of the Peruvian Amazon. Faculty of Agronomy, located in the community of Zungarococha, which has the title "Agronomic characteristics of four forage tree species in the Zungarococha Estate, Iquitos - Peru" The evaluation was used the design of Complete Randomized Block with four treatments and four repetitions where treatment T1 is Erythrina sp., T2 Leucaena leucocephala cv CUNNINGHAM, T3 Gliricidia sepium and T4 Morus nigra, reaching the following conclusions, for the dependent variable of the agronomic characteristics at the 9th week in plant height, percentage of cover, green matter, and dry matter the treatment T1 Erythrina sp (amasisa), occupied the first with 1.29 m, 84.40%, 3.11 kg / m2 and 0.78 kg / m2. Second place was occupied by T4: Morus nigra (mulberry), with averages of 1.28 m, 83.35%, 2.94 kg/m2 and 0.75 kg/m2. The fertilizer used and the amount of fertilizer plays an important role over time in the forage yield of these forage tree species.